Ethnic Discrimination and Signals of Trustworthiness in an Online Market: Evidence from Two Field Experiments - Przepiorka, W (2011)
Results of two field experiments which were designed to identify possible ethnic discrimination on a German internet auction platform are discussed. A first set of results was produced by a secondary analysis of an earlier experiment. The second experiment then tested whether costly signals could help to overcome problems of trust between buyers and sellers in online markets. The evidence is rather mixed with respect to ethnic discrimination, and it does not support the signaling hypothesis. © Lucius and Lucius Verlag Stuttgart.